The complete chloroplast genome sequence of Brachypodium sylvaticum - Yunqiang Wang; Yi Wang; Xiaolong Yuan; Yunqin Li; Qinghua Wang (Mitochondrial DNA. Part B. Resources, 2021)
The first complete chloroplast genome (cpDNA) sequence of Brachypodium sylvaticum was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 136,392 bp in length, contains a large single-copy region (LSC) of 80,854 bp and a small single-copy region (SSC) of 12,765 bp, which were separated by a pair of inverted repeats (IR) regions of 21,383 bp. The genome contains 130 genes, including 84 protein-coding genes, 8 ribosomal RNA genes, and 38 transfer RNA genes. Further phylogenomic analysis showed that B. sylvaticum and B. distachyon clustered in a unique clade in Brachypodium genus.